Introduction and summary to the Handbook of Trade Policy and WTO Accession for Development in Russia and the CIS - Tarr, David (World Bank, Washington, DC, 2012)
This paper is the introduction and summary chapter of the 43 chapter volume entitled Handbook of Trade Policy and WTO Accession for Development in Russia and the CIS. The key policy conclusions of each of the chapters are highlighted in this paper. The Handbook will be published only in Russian in 2005, but an English language version of the majority of the papers described here is available on the website www.worldbank.org/trade/russia-wto. This paper first explains the potential importance of World Trade Organization (WTO) accession as a development tool, and discusses the recent successful development models and the role of trade policy in their development. The paper then summarizes the three parts of the Handbook. The first part treats trade policy (with applications to Russia and the Commonwealth of Independent States [CIS]). The second part treats World Trade Organization institutions and disciplines, again with Russia and CIS applications. And the third part focuses on various aspects of the impact of WTO accession on Russia. The numerous papers that relate trade policy and WTO accession to experience in Russia and the CIS are likely to be of special interest to native English speakers, since these papers are new to the literature. The papers in the Handbook are intended to be non-technical materials accessible to a wide policy audience. The Handbook forms the basis of a World Bank Institute course on trade policy and WTO accession, which has been delivered and will be delivered again on multiple occasions.